A web-based intervention for users of amphetamine-type stimulants: 3-month outcomes of randomized controlled trial - Tait, Robert; McKetin, R.; Kay-Lambkin, F.; Carron-Arthur, B.; Bennett, A.; Bennett, K.; Christensen, H.; Griffiths, K. (JMIR Publications, 2014)
Background: Among illicit drugs, the prevalence of amphetamine-type stimulant (ATS) use is second only to cannabis. Currently, there are no approved pharmacotherapies for ATS problems, but some face-to-face psychotherapies are effective. Web-based interventions have proven to be effective for some substance use problems, but none has specifically targeted ATS users. Objective: The objective of the study was to evaluate the effectiveness of a Web-based intervention for ATS problems on a free-to-access site compared with a waitlist control group. Methods: We used a randomized controlled trial design. The primary outcome measure was self-reported ATS use in the past three months assessed using the Alcohol, Smoking, Substance Involvement Screening Test (ASSIST). Other measures included quality of life (EUROHIS score), psychological distress (K-10 score), days out of role, poly-drug use, general help-seeking intentions, actual help-seeking, and “readiness to change”. The intervention consisted of three fully automated, self-guided modules based on cognitive behavioral therapy and motivation enhancement. The analysis was an intention-to-treat analysis using generalized estimating equation models, with a group by time interaction as the critical assessment.Results: We randomized 160 people (intervention n=81, control n=79). At three months, 35/81 (43%) intervention and 45/79 (57%) control participants provided follow-up data. In the intervention group, 51/81 (63%) completed at least one module. The only significant group by time interaction was for days out of role. The pre/post change effect sizes showed small changes (range d=0.14 to 0.40) favoring the intervention group for poly-drug use, distress, actual help-seeking, and days out of role. In contrast, the control group was favored by reductions in ATS use, improvements in quality of life, and increases in help-seeking intentions (range d=0.09 to 0.16). Conclusions: This Web-based intervention for ATS use produced few significant changes in outcome measures. There were moderate, but nonsignificant reductions in poly-drug use, distress, days partially out of role, and increases in help-seeking. However, high levels of participant attrition, plus low levels of engagement with the modules, preclude firm conclusions being drawn on the efficacy of the intervention and emphasize the problems of engaging this group of clients in a fully automated program.